Metahuman Futures Manifesto - Chorus, MFF 2022 Lesvos Assembly (Journal of Posthumanism, 2023)
The Metahuman Futures Manifesto has been revised and approved by the Lesvos Metahuman Futures Assembly-Chorus, following the first draft discussed at 1st Metahuman Futures Forum in Lesvos in 2022.